2019
DOI: 10.1161/atvbaha.118.312186
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Enhances Vascular Smooth Muscle Cell Proliferation and Development of Neointimal Hyperplasia

Abstract: Objective— Dysregulated proliferation of vascular smooth muscle cells (VSMC) plays an essential role in neointimal hyperplasia. CD36 functions critically in atherogenesis and thrombosis. We hypothesize that CD36 regulates VSMC proliferation and contributes to the development of obstructive vascular diseases. Approach and Results— We found by immunofluorescent staining that CD36 was highly expressed in human vessels with obstructive diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 65 publications
1
18
0
Order By: Relevance
“…Both MMP-2 and MMP-9 can activate VSMCs to promote the production of new collagen. 15,16 The study showed that in neointima MMP-2 and MMP-9 were positively correlated with the amount of new collagen during the neointimal regression period. This suggests that the reduction of MMP-2 and MMP-9 in neointima might, in part, contribute to the decrease in the amount of new collagen during this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both MMP-2 and MMP-9 can activate VSMCs to promote the production of new collagen. 15,16 The study showed that in neointima MMP-2 and MMP-9 were positively correlated with the amount of new collagen during the neointimal regression period. This suggests that the reduction of MMP-2 and MMP-9 in neointima might, in part, contribute to the decrease in the amount of new collagen during this period.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 This partly explains this chronological sequence. MMP-2 and MMP-9 can activate VSMCs to proliferate and express collagen, 15,16 and the collagen accumulation phase was more prolonged than the VSMC proliferation phase, 17 so the accumulation of collagen reached a maximum even if the expression of MMP-2 and MMP-9 was low at 56 days. In this study, the changing trend of MMP-2 and MMP-9 is consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activated platelets internalize oxLDL, while platelets loaded with oxLDL further activate the endothelium, release chemokines to recruit monocytes, and promote foam cell development [ 38 ]. CD36 deficiency in ApoE −/− mice can inhibit neointimal hyperplasia and vascular smooth muscle cells (VSMCs) proliferation, which may prevent atherosclerosis and restenosis [ 39 ]. Lectin-like oxidized LDL receptor 1 (LOX-1) was identified as another major receptor of oxLDL in human platelets [ 40 ].…”
Section: Platelets and Risk Factors Of Atherosclerosismentioning
confidence: 99%
“…71 CD36 promotes VSMC proliferation via the upregulation of cyclin A expression and increases dedifferentiated VSMC phenotypes via the inhibition of STAT 3 activity. 72…”
Section: Other Stat3 Signaling Pathwaysmentioning
confidence: 99%